2016
DOI: 10.1016/j.jimonfin.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Taylor rule deviations and out-of-sample exchange rate predictability

Abstract: The Taylor rule has become the dominant model for academic evaluation of out-of-sample exchange rate predictability. Two versions of the Taylor rule model are the Taylor rule fundamentals model, where the variables that enter the Taylor rule are used to forecast exchange rate changes, and the Taylor rule differentials model, where a Taylor rule with postulated coefficients is used in the forecasting regression. We use data from 1973 to 2014 to evaluate short-run out-ofsample predictability for eight exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…They incorporated the financial crisis into their work and found that the Taylor rule fundamentals have the power to predict the exchange rate. Ince et al (2016) extended the work by Molodtsova and Papell (2009) and demonstrated short-run out-of-sample predictability of the exchange rate with the two versions of the Taylor rule model for eight exchange rates vis-à-vis the U.S. dollar. Their research found strong evidence of exchange rate predictability with the Taylor rule fundamental model as compared to the Taylor rule differential and much stronger proof than the traditional exchange rate predictors.…”
Section: Literature Reviewmentioning
confidence: 76%
See 2 more Smart Citations
“…They incorporated the financial crisis into their work and found that the Taylor rule fundamentals have the power to predict the exchange rate. Ince et al (2016) extended the work by Molodtsova and Papell (2009) and demonstrated short-run out-of-sample predictability of the exchange rate with the two versions of the Taylor rule model for eight exchange rates vis-à-vis the U.S. dollar. Their research found strong evidence of exchange rate predictability with the Taylor rule fundamental model as compared to the Taylor rule differential and much stronger proof than the traditional exchange rate predictors.…”
Section: Literature Reviewmentioning
confidence: 76%
“…Molodtsova and Papell (2012) examined the USD/EUR exchange rate during the financial crisis and found that the Taylor rule fundamental could still predict the exchange. Ince et al (2016) also proved the predictability of the Taylor rule fundamentals during the financial crisis and the great recession for eight countries.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The literature shows the different fit results after applying different statistical techniques and Monte Carlo algorithms for these Currency Market models. For example, models constructed with linear statistical techniques, such as Ordinary Least Squares, linear regression methods, and Factor models, have provided an adjustment of 0.93-1.84 standard deviation (Rossi, 2013;Park and Park, 2013;Byrnea et al, 2016;Ince et al, 2016;Serjam and Sakurai, 2018), but their adjustments are between 1.26-2.11 when constructed with small samples (Rossi, 2013;Jacob and Uusküla, 2019). On the other hand, other more advanced statistical models, especially non-linear models, such as Vector Autoregression, time-varying parameter models, and Error Correction models.…”
mentioning
confidence: 99%
“…Byrne et al (2016) applied the Time-Varying Parameters method, for a sample of several OECD currencies per US dollar, obtaining an overall standard deviation of 0.72. Ince et al (2016) used ordinary least squares (OLS) to estimate theoretical models of the FOREX market for data on US dollar-Swiss franc and US dollar-Japanese Yen exchange rates. They got an overall standard deviation superior to 1.06 in their estimates.…”
mentioning
confidence: 99%